TRADITIONAL CULTURAL EXPRESSIONS BOTH WITHIN AND BEYOND THE CONTEXT OF INTELLECTUAL PROPERTY LAW IN INDONESIA - Melisa Safitri (Faculty of Law-Universitas Bandar Lampung, 2022)
Can TCEs crumble under the protection of intellectual property? This question is prompted by the disparity between the characteristics of TCEs and the intellectual property protection criteria. This article emphasize the necessity and significance of establishing a system outside the Intellectual Property system or special protection (sui generis) to protect TCEs because intellectual property law cannot be modified to accommodate TCEs. The law of intellectual property only protects the moral and economic rights of individuals, not cultural or communal rights. Other opinions contend that the existing intellectual property law, particularly copyright law, does not require a new system because the creation of another system is a waste of resources and the state may not be able to fund it. In reality, what must be taken into account is the extent to which ethnic communities control their TCEs.